Communication in vertical markets: Experimental evidence - Claudia Möllers; Hans-Theo Normann; Christopher M. Snyder (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
When an upstream monopolist supplies several competing downstreamfirms, it may fail to monopolize the market because it is unable to commit not to behave opportunistically. We build on previous experimental studies of this well-known commitment problem by introducing communication. Allowing the upstream firm to chat privately with each downstream firm reduces total offered quantity from near the Cournot level (observed in the absence of communication) halfway toward the monopoly level. Allowing all three firms to chat together openly results in complete monopolization. Downstream firms obtain such a bargaining advantage from open communication that all of the gains from monopolizing the market accrue to them. A simple structural model of Nash-in-Nash bargaining fits the pattern of shifting surpluses well. Using third-party coders, unsupervised text mining, among other approaches, we uncover features of the rich chat data that are correlated with market outcomes. We conclude with a discussion of the antitrust implications of open communication in vertical markets.
Keywords: L42; K21; C90; C70; 330; commitment; communication; experiments; vertical restraints